Improving the odds : developing powerful teaching practice and a culture of learning in urban high schools - Del Prete, Thomas (The series on school reform, 2010)
"A counterpoint to the sweeping rhetoric of reform, this book offers a nuanced depiction of the challenges and possibilities at the school and class-room level. Through the experiences of urban high school teachers who partner with their local university, Del Prete provides unique insight into teaching and learning in the midst of reform."--BOOK JACKET